2019
DOI: 10.31703/gssr.2019(iv-ii).07
|View full text |Cite
|
Sign up to set email alerts
|

Comforting Investments are Rarely Profitable: Impediments in Investor Decision Making

Abstract: This research aims at testing and confirming existence of selected behavioral biases of investors that affect their decisions. Five behavioral biases affecting irrational behavior of investors were selected: overconfidence bias, illusion of control bias, confirmation bias and recency bias and optimism bias. Primary data was collected through a questionnaire from 300 investors from banks, insurance companies, stock exchanges etc. The results were obtained by employing a correlation and regression analysis for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
(11 reference statements)
0
3
0
2
Order By: Relevance
“…This suggests that investors' feelings and beliefs influence their investment decision- making (Dhaoui and Khraief, 2014). Bashir et al , (2019) reported an insignificant relationship between optimism and investor decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This suggests that investors' feelings and beliefs influence their investment decision- making (Dhaoui and Khraief, 2014). Bashir et al , (2019) reported an insignificant relationship between optimism and investor decision-making.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Amidu et al (2008) characterized anchoring as a form of bias caused by an appraiser's adjustments of an initial anchor, and such adjustments are often insufficient to compensate for the effects of the initial reference point, thereby reducing the accuracy of judgment. According to Bashir et al (2019), decision-makers often neglect the possibility of making misjudgments and are easily influenced by multiple biased and erroneous factors. Iroham et al (2013) demonstrated that utilizing anchoring would result in the inconsistency and inaccuracy of estimations.…”
Section: Questionnaire Designmentioning
confidence: 99%
“…Therefore, in addition to increasing appraisers' self-discipline, appraiser associations should establish higher standards for ethical norms and implement clear and quick supervisory measures. Finally, concerning the psychological and cognitive aspects, Bashir et al (2019) highlighted that behavioral biases are associated with feelings, perceptions, affection, intelligence, and personality. Pompian (2012) classified behavioral biases into cognitive errors and emotional biases and noted that the former can be corrected more easily than the latter.…”
Section: Practical Implicationsmentioning
confidence: 99%
“…Hasil penelitian menunjukkan optimism bias tidak signifikan terhadap keputusan investasi investor saham di kota Palembang dan hal ini mendukung penelitian Bashir et al (2019) serta Riaz & Iqbal (2015). Investor mempertimbangkan pengambilan keputusan dengan informasi yang diperolehnya dengan hati-hati dan menggunakan informasi yang mendukung guna melengkapi informasi yang dianggap bertentangan.…”
Section: Hasil Ujiunclassified
“…Penelitian Pradhana (2018) danBashir et al (2019) menyimpulkan illusion of control bias memiliki hubungan signifikan terhadap keputusan investasi, sehingga diperoleh hipotesis: H5: Illusion of Control bias signifikan terhadap pengambilan keputusan investasi.…”
unclassified